Banana bunchy top virus threat to African bananas - Kumar, P. Lava (Food and Agriculture Organization of the United Nations, 2022)
The banana bunchy top virus (BBTV) is threatening livelihoods and banana biodiversity in sub-Saharan Africa. Since the first report in the 1960s, the virus has spread to 17 countries, eight of those in the last decade, including a recent spread in Uganda and Tanzania. In the "2022 International Plant Protection Convention Regional Workshop for Africa," organized by the FAO-IPPC, the African Union-Inter-African Phytosanitary Council (AU-IAPSC), the Plant Protection Organization of Kenya (KEPHIS), and FAO, the BBTV emergence in EA, along with other emerging threats in Africa, was discussed to strategies control actions. The event was held in a hybrid format from 6-8 Sep-2022 in Nairobi and was attended by 58 participants from 22 countries. The summary of BBTV status and recommendations for control was made through the presentation. It has led to the FAO allocation of emergency funds for BBTV management in EA through TCP (Technical Action Program) for 2023.